Cell-penetrating peptide-conjugated copper complexes for redox-mediated anticancer therapy - Peña, Quim; Rodríguez-Calado, Sergi; Simaan, A. Jalila; Capdevila, Mercè; Bayón, Pau; Palacios, Oscar; Lorenzo, Julia; Iranzo, Olga (Frontiers in Pharmacology, 2022)
Metal-based chemotherapeutics like cisplatin are widely employed in cancer treatment. In the last years, the design of redox-active (transition) metal complexes, such as of copper (Cu), has attracted high interest as alternatives to overcome platinum-induced side-effects. However, several challenges are still faced, including optimal aqueous solubility and efficient intracellular delivery, and strategies like the use of cell-penetrating peptides have been encouraging. In this context, we previously designed a Cu(II) scaffold that exhibited significant reactive oxygen species (ROS)-mediated cytotoxicity. Herein, we build upon the promising Cu(II) redox-active metallic core and aim to potentiate its anticancer activity by rationally tailoring it with solubility- and uptake-enhancing functionalizations that do not alter the ROS-generating Cu(II) center. To this end, sulfonate, arginine and arginine-rich cell-penetrating peptide (CPP) derivatives have been prepared and characterized, and all the resulting complexes preserved the parent Cu(II) coordination core, thereby maintaining its reported redox capabilities. Comparative in vitro assays in several cancer cell lines reveal that while specific solubility-targeting derivatizations (i.e., sulfonate or arginine) did not translate into an improved cytotoxicity, increased intracellular copper delivery via CPP-conjugation promoted an enhanced and significantly faster anticancer activity. Additionally, immunofluorescence assays show that the Cu(II) peptide-conjugate distributed throughout the cytosol without lysosomal colocalization, suggesting potential avoidance of endosomal entrapment. Overall, the systematic exploration of the tailored modifications enables us to provide further understanding on structure-activity relationships of redox-active metal-based (Cu(II)) cytotoxic complexes, which contributes to rationalize and improve the design of more efficient redox-mediated metal-based anticancer therapy.